Synthetic Peptides as Immunogen in the Production of IgY Anti-C-Myc Antibody in Local Chicken (Gallus Gallus) - Salomo Hutahaean (International Journal of Ecophysiology, 2019)
Experiments conducted to determine the effect of doses of immunogen on the levels of IgY c-Myc antibody in chickens. To generate antibody, we used a synthetic peptide as an immunogen, which is developed from the epitope of the c-Myc protein. Hens were immunized a week after their first eggs were produced. Antigen diluted in double distilled water and emulsified with Freund 's Complete Adjuvant. The suspension was injected into the area of the chicken breast subcutaneously with a dose of 0, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, or 0.16 mg per hen. Booster injection performed on days 10, 20, and 30 with the same volume of emulsion, but using Incomplete Freund 's Adjuvant and the amount of antigen was half of the amount of the first Immunization. Extraction of IgY from eggs was carried out using kits from Gallus Immunotech. The level of IgY was quantified using a spectrophotometer where the absorbance was read at 280 nm. The results showed that after the first immunization IgY content of the egg were reached the level of >5 mg/ml yolk when the dose of immunogen was above 0.1 mg/hen. The level was higher in eggs produced after the third booster ( >8 mg/ml yolk), but it is lower in all groups treated with immunogen above 0.1 mg/hen. We concluded, immunogen dosage of 0.1 mg/hen was optimum in the production of chicken IgY anti-c-Myc.